2023
DOI: 10.1002/smll.202301385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanomedicine in Women's Metastatic Breast Cancer

Abstract: Metastatic breast cancer is responsible for 90% of mortalities among women suffering from various types of breast cancers. Traditional cancer treatments such as chemotherapy and radiation therapy can cause significant side effects and may not be effective in many cases. However, recent advances in nanomedicine have shown great promise in the treatment of metastatic breast cancer. For example, nanomedicine demonstrated robust capacity in detection of metastatic cancers at early stages (i.e., before the metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 251 publications
0
3
0
Order By: Relevance
“…Polymers and nanostructures offer platforms that can operate safely in living systems [1][2][3], enabling the development of localized treatments with enhanced efficacy [4][5][6]. The advantage of these structures is the biocompatible scaffold combined with the possibility to host different types of therapeutic payloads [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers and nanostructures offer platforms that can operate safely in living systems [1][2][3], enabling the development of localized treatments with enhanced efficacy [4][5][6]. The advantage of these structures is the biocompatible scaffold combined with the possibility to host different types of therapeutic payloads [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have developed novel drug delivery systems to enhance tumor cell ablation and reduce side effects. 16 Studies have shown that nanocarrier-based Dox delivery can reduce drug protein interactions, achieve selective Dox accumulation at tumor sites, and alleviate systemic toxicity. 17 Thus, various Dox encapsulated nanomedicines have been developed for cancer treatment, including polymeric and liposomal nanoparticles as well as other inorganic nanosystems.…”
mentioning
confidence: 99%
“…Recent advances in nanomedicine have shown great promise in the treatment of breast cancer. Several researchers have developed novel drug delivery systems to enhance tumor cell ablation and reduce side effects . Studies have shown that nanocarrier-based Dox delivery can reduce drug protein interactions, achieve selective Dox accumulation at tumor sites, and alleviate systemic toxicity .…”
mentioning
confidence: 99%